The impact of changing provider remuneration on clinical activity and quality of care: Evaluation of a pilot NHS contract in Northern Ireland. Issue 5 (14th June 2020) - Hill, Harry; Howarth, Elizabeth; Walsh, Tanya; Tickle, Martin; Birch, Stephen; Brocklehurst, Paul
Abstract: Objectives: A pilot NHS dental contract was introduced in Northern Ireland between 2015 and 2016, which involved changing the method for paying general dental practitioners working in the NHS from fee‐for‐service (FFS) to capitation‐based payments, providing an opportunity for a robust evaluation. We investigated the impact of a change in payment methods on clinical activity and the quality of care provided. Design: A difference‐in‐difference (DiD) evaluation was applied to clinical activity data from pilot NHS dental practices in Northern Ireland compared to matched control NHS practices and applied to a questionnaire survey of patient‐rated outcomes of health outcomes and care quality. We estimated the impact on access to care, treatment activity levels, practice finances and patient‐rated outcomes of care of a change from FFS to a capitation‐based system for 1 year, as well as the impact of a reversion back to FFS at the end of the pilot period. Results: The monthly number of registered patients in the pilot practices increased more than the control practices during the capitation period, by 1.5 registrations per 1000 registered patients. The monthly reductions in the volumes of all treatments in the pilot practices during the capitation period were much larger than the control practices, with 175 fewer treatment items. All measures rapidly returned to baseline levels following reversion from capitation back to FFS. NHS income per month increased in pilot practices, by £5920 per month (calculated on FFS item cost basis) more than controls in the capitation period. The analysis of patient questionnaires suggest found that patients notice differences only in waiting times, skill‐mix and number of radiographs, but not on other measures of healthcare process and quality. Conclusion: General dental practitioners working in the NHS respond rapidly and consistently to changes in provider payment methods. A move from FFS to a capitation‐based system had little impact on access to care, but did produce large reductions in clinical activity and patient charge income. Patients noticed little change in the service they received. This shows that changes in remuneration contracts have the potential to meet policy goals, such as meeting the expectations of patients within a predictable cost envelope. However, it is unlikely that all policy goals can be met simply by changing payment methods. Therefore, work is also needed to identify and evaluate interventions that can complement changes in remuneration to achieve desirable outcomes.